2014
DOI: 10.9738/intsurg-d-13-00115.1
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Metastasis From Renal Cell Carcinoma With Gastrointestinal Bleeding: A Case Report and Review of the Literature

Abstract: A 61-year-old man presented to our hospital with hypercalcemia and elevated C reactive protein (CRP). Evaluation revealed renal cell carcinoma (RCC) with metastasis to lung, bone, and brain. He underwent partial resection of the right kidney and a left nephrectomy. Histopathologic findings of resected tumors were consistent with clear cell RCC. Whole-brain irradiation was performed for management of brain metastasis. Postoperatively, he was treated with molecularly targeted therapy using a mammalian target of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 24 publications
2
34
0
Order By: Relevance
“…[1,3] Up to now we could detect only a total of 50 cases in the literature. [1][2][3][4][5][6][7][8][9][10][11][12] In only 4 of these cases gastric metastases developed 20 or more years after diagnosis of renal cell carcinoma. [5,8,12] In this article we presented the 5 th case with gastric metastasis of renal cell carcinoma 20 years after he had undergone radical nephrectomy because of renal cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…[1,3] Up to now we could detect only a total of 50 cases in the literature. [1][2][3][4][5][6][7][8][9][10][11][12] In only 4 of these cases gastric metastases developed 20 or more years after diagnosis of renal cell carcinoma. [5,8,12] In this article we presented the 5 th case with gastric metastasis of renal cell carcinoma 20 years after he had undergone radical nephrectomy because of renal cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] In our study, we report a case of RCC with metastases to the right psoas, paravertebral, and gluteus medius muscles after 4 years right side radical nephrectomy. We wish to emphasize the magnetic resonance imaging (MRI) features of metastatic RCC to the skeletal muscles.…”
mentioning
confidence: 99%
“…2 Making a diagnosis of metastatic RCC to the skeletal muscle is challenging, because the site is unpredictable, in addition to it being rare, a recent review of the literature revealed some cases. [2][3][4][5] In our study, we report a case of RCC with metastases to the right psoas, paravertebral, and gluteus medius muscles after 4 years right side radical nephrectomy. We wish to emphasize the magnetic resonance imaging (MRI) features of metastatic RCC to the skeletal muscles.…”
mentioning
confidence: 99%
See 2 more Smart Citations